2015
DOI: 10.3748/wjg.v21.i20.6252
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of benign and malignant branch duct intraductal papillary mucinous neoplasm using contrast-enhanced endoscopic ultrasonography

Abstract: Using CE-EUS to measure MN height provides a highly accurate method for differentiating benign from malignant BD-IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 36 publications
0
60
0
1
Order By: Relevance
“…EUS, despite the high number of studies published showing its good diagnostic accuracy in PCNs [12][13][14][15][16][17][18][19][20][21], is recommended as an adjunct imaging modality in the European guidelines [3]. Several studies [5,[15][16][17] have shown that the diameter of the main pancreatic duct or a nodule at the time of diagnosis is a predictor of malignant IPMN. Fine needle aspiration (FNA) is an adjunctive procedure performed during EUS that is helpful in reaching a conclusive diagnosis as it allows the aspiration of cystic fluid or tissue collection of a nodule.…”
Section: Discussionmentioning
confidence: 99%
“…EUS, despite the high number of studies published showing its good diagnostic accuracy in PCNs [12][13][14][15][16][17][18][19][20][21], is recommended as an adjunct imaging modality in the European guidelines [3]. Several studies [5,[15][16][17] have shown that the diameter of the main pancreatic duct or a nodule at the time of diagnosis is a predictor of malignant IPMN. Fine needle aspiration (FNA) is an adjunctive procedure performed during EUS that is helpful in reaching a conclusive diagnosis as it allows the aspiration of cystic fluid or tissue collection of a nodule.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of CH‐EUS is its inability to differentiate between serous and mucinous cysts because their enhancement patterns are similar, although CH‐EUS was able to distinguish between pseudocysts and other pancreatic cysts . CH‐EUS assessment of MN height cut‐off value has also been analyzed . For example, the optimum cut‐off value of MN height was found to be 8.8 mm for diagnosing malignant IPMN, with this height having an accuracy of 93% .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies evaluated the utility of CH-EUS for diagnosing pancreatic cystic lesions ( Table 2). [47][48][49][50][51][52][53][54][55] Detection by B-mode EUS of MN-like structures in dilated pancreatic ducts of patients with IPMN may result in difficulties determining whether these structures are mucous clots or MN. However, CH-EUS can distinguish these structures by evaluating the presence or the absence of blood flow in the lesion 47,48 (Figs 1 and 2).…”
Section: Endoscopic Ultrasound-through-the-needle Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast-enhanced harmonic (CH)-EUS has been reported also as a useful tool. This technology allows for blood flow assessment in PCLs and better identification of mural nodules, which can be helpful in differentiating between benign, premalignant or malignant lesions with more accuracy [23,24]. EUS elastography is a noninvasive technology that has been recently studied in PCLs, it can be of value in differentiating between serous and mucinous cystic lesions by measuring ultrasound acoustic radiation by force impulse quantification [25].…”
Section: • • Pancreatic Cystic Lesions and The Importance Of Endoscopymentioning
confidence: 99%